From Headline to Hard Grind: The Importance of Understanding Public Administration in Achieving Health Outcomes Comment on "Understanding the Role of Public Administration in Implementing Action on the Social Determinants of Health and Health Inequities" - Janine O'Flynn (Kerman University of Medical Sciences, 2016)
Many public policy programs fail to translate ambitious headlines to on-the-ground action. The reasons for this are many and varied, but for public administration and management scholars a large part of the gap between ambition and achievement is the challenge associated with the operation of the machinery of government itself, and how it relates to the other parties that it relies on to fulfill these outcomes. In their article, Carey and Friel set out key reasons why public health scholars should seek to better understand important ideas in public administration. In commenting on their contribution, I draw out two critical questions that are raised by this discussion: (i) what are boundaries and what forms do they take? and (ii) why work across boundaries? Expanding on these key questions extends the points made by Carey and Friel on the importance of understanding public administration and will better place public health scholars and practitioners to realise health outcomes.